Nurse practitioner prescribing practice in Australia: Confidence in aspects of medication management. Issue 1 (February 2014) - Cashin, Andrew; Stasa, Helen; Dunn, Sandra V; Pont, Lisa; Buckley, Thomas
<x xml:space="preserve">Abstract</x> The findings of the 2010 national survey of nurse practitioner (NP) prescribing in Australia related to confidence in prescribing are reported. A significant correlation between years endorsed as a NP and prescribing confidence was found. NPs in Australia were significantly more confident in the prescribing aspects of commencing a new medication than adjusting or ceasing a medication prescribed by others. These findings are discussed in relation to promotion of the quality use of medicines and identification of potential strategies to promote the ongoing positive evolution of NP practice in Australia.